The Relationship between Antithyroid Antibody and Pregnancy Outcome in Invitro Fertilization and Embryo Transfer - Fawz Alaa alikhan1 , Azhar Mousa AL-Turiahi, 2 Asceel Hassan Bader3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background of the study: One type of assisted reproductive technique is intracytoplasmic sperm injection(ICSI) Despite use ofintracytoplasmic sperm injectionICSI it remain has low birth rate due to failurerate there are many markers associated with poor predict the outcome one of these factor effect outcomeinintracytoplasmic sperm injection ICSI presence of antithyroid antibody ineuthyroid patientAim of study: To examine the effect of antithyroid antibody on pregnancy results following the in vitrofertilization and fetus transmitMethods and patients : Cross section study conducted at AL-Sader infertility center atotal of eighty oneIraqi women were enrolled in this study of them 22positive antithyroid antibody,59 negative antithyroidantibody were undergone intra-cytoplasmic sperm injection ICSI in Al-Sader infertility center. The group ofthe study involved onlyeuthyroid women outwardly any clinically showed autoimmune illness.Result:there was higher significant difference p value<0.004 in fertilization rate number of availableembryos p value<0.003 and number of transfer embryos p value< 0.001among study group which washigher in group of women with antithyroid negative followed by,group with antithyroid positive in infertileeuthyroid women Conclusion:patients with antithyroid antibody associated with poor pregnancy outcomein infertile euthyroid women undergoingintracytoplasmic sperm injection ICSI